2015
DOI: 10.1111/ijd.12967
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the CYP2D6 gene polymorphism on the risk of pemphigoid

Abstract: The study results may suggest the impact of CYP2D6 gene polymorphism (A2637 deletion) on a higher prevalence of bullous pemphigoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Like in MMP, there is also still a paucity in the identification of gene polymorphisms predisposing to BP. Susceptibility to BP has been associated with SNPs in IL1B , the gene for IL‐1β, in a Chinese cohort and in CYP2D6 , the gene for the cytochrome P450 oxidase 2D6, in a Polish cohort . In addition, copy number variations (CNVs) in the Fcγ receptor genes FCGR2B and FCGR3B as well as polymorphisms in the mitochondrial gene ATP8 have been associated with the risk for BP in a German cohort .…”
Section: Discussionmentioning
confidence: 99%
“…Like in MMP, there is also still a paucity in the identification of gene polymorphisms predisposing to BP. Susceptibility to BP has been associated with SNPs in IL1B , the gene for IL‐1β, in a Chinese cohort and in CYP2D6 , the gene for the cytochrome P450 oxidase 2D6, in a Polish cohort . In addition, copy number variations (CNVs) in the Fcγ receptor genes FCGR2B and FCGR3B as well as polymorphisms in the mitochondrial gene ATP8 have been associated with the risk for BP in a German cohort .…”
Section: Discussionmentioning
confidence: 99%
“…Studies for single nucleotide polymorphisms have been defined several psoriasis susceptibility genes ( 130 , 133 ) (Table 1 ) whereas it has been challenging to identify the susceptibility genes of pemphigus or pemphigoid diseases and there is much less information about their susceptibility genes. As for two major bullous diseases that can be associated with psoriasis, following genes are suggested to be associated with the disease susceptibility:, IL1B ( 135 ), CD16 ( 136 ), ATP8 ( 137 ), and CYP2D6 ( 138 ) in bullous pemphigoid; and CD40L, CD40, BLYS ( 139 ), CTLA4 ( 140 ), and CD59 ( 141 ) in pemphigus foliaceus. However, they are not included in the major psoriasis susceptibility genes except for the risk loci at IL1B in late onset psoriasis ( 142 ).…”
Section: Susceptibilities Of Psoriasis and Bullous Diseasesmentioning
confidence: 99%
“…A German study showed that a polymorphism in the mitochondrially encoded ATP synthase 8 gene ( MT-ATP8 ) may have an association with BP pathogenesis, which suggests a contribution of mitochondrial abnormalities to BP immunopathology 44 . Furthermore, a recent study showed that gene polymorphism in CYP2D6 , which is among the cytochrome P450 isoenzymes, may influence the risk of drug-induced BP 45 . Dipeptidyl peptidase-IV (DPP-4) inhibitors have been increasingly implicated as a cause of drug-induced BP.…”
Section: Pemphigoidmentioning
confidence: 99%